2019
DOI: 10.1002/art.40773
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Murine Lupus by CD4+ and CD8+ Treg Cells Induced by T Cell–Targeted Nanoparticles Loaded With Interleukin‐2 and Transforming Growth Factor β

Abstract: Objective. To develop a nanoparticle (NP) platform that can expand both CD4+ and CD8+ Treg cells in vivo for the suppression of autoimmune responses in systemic lupus erythematosus (SLE).Methods. Poly(lactic-co-glycolic acid) (PLGA) NPs encapsulating interleukin-2 (IL-2) and transforming growth factor β (TGFβ) were coated with anti-CD2/CD4 antibodies and administered to mice with lupus-like disease induced by the transfer of DBA/2 T cells into (C57BL/6 × DBA/2)F 1 (BDF1) mice. The peripheral frequency of Treg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 44 publications
4
58
0
Order By: Relevance
“…Nanoparticles (NPs) encapsulating peptides represent a potential modality to carry Tregs. It is reported that NPs encapsulating IL‐2 and TGF‐β coated with anti‐CD2/CD4 antibodies resulted in an expansion of Tregs in vivo and alleviated SLE phenotypes in mouse models 51 …”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticles (NPs) encapsulating peptides represent a potential modality to carry Tregs. It is reported that NPs encapsulating IL‐2 and TGF‐β coated with anti‐CD2/CD4 antibodies resulted in an expansion of Tregs in vivo and alleviated SLE phenotypes in mouse models 51 …”
Section: Resultsmentioning
confidence: 99%
“…In a model of skin transplantation in mice, CD8 + CD122 + PD-1 + Tregs expanded ex vivo combined with costimulation blockade of CD40/CD154, but not of B7/CD28, synergizing to prolong the allograft survival in an IL-10-dependent manner. 139 Cytokine therapies such as the one using IL-34 has been shown to also modulate the Treg/Teff balance by differentiating monocytes into regulatory macrophages that could in turn induce CD8 + and CD4 + Tregs responsible for the long-term tolerogenic effect. Simultaneous blockade of the CD40/CD40L and CD28/B7 interactions using CD40Ig and anti-CD28 mAbs abrogated in 50% of the recipients tolerance, inhibited CD8 + Treg induction and modified the regulatory mechanisms taking place in the remaining recipients that did not reject their allograft, 138 suggesting that the B7/CD28 costimulation is required for CD8 + Treg expansion and function.…”
Section: Originmentioning
confidence: 99%
“…We have similar unpublished results in a model of GVHD in rats and nod scid gamma (NSG) mice and in a model of lupus (unpublished data). In a lupus model in mice, administration of T cell targeting nanoparticles loaded with IL-2 and TGFβ significantly expanded CD4 + and CD8 + Tregs that could reduce the disease 139.…”
mentioning
confidence: 99%
“…A number of studies have investigated the effect of nanocarrier-encapsulated IL-2 on the immune system ( Figure 4 ). For this purpose, IL-2 was loaded into liposomes [ 70 ], poly(milk-co-glycolic) (PGLA) particles [ 71 , 72 ], poly n-(2-hydroxypropyl)methacrylamide (HPMA) particles [ 73 ], Chitosan nanoparticles [ 74 ], or bundled carbon nanotubes [ 75 ]. In some of the studies, the nanocarriers were combined with other substances, including doxorubicin [ 74 ], TGF- α [ 71 ], a TGF-α inhibitor [ 70 ], or peptide-MHC complexes [ 76 ].…”
Section: Il-2 and Its Initial Use In Cancer Therapymentioning
confidence: 99%